Desenvolvimento de blendas de TPS, PCL E PLA e seus nanocompósitos com nanowhiskers de celulose de gravatá - Carmona, Vitor Brait (2015)
The objective of this project was the study of polymer blends of thermoplastic starch (TPS), poly(ε-caprolactone) (PCL) and poly(lactic acid) (PLA) and the extraction of celulose nanowhisker from gravatá (Bromelia balansae) (NWCg) and macaúba (Acrocomia aculeata) (NWCm) for the development of biodegradable nanocomposites. Firstly, binary and ternary polymer blends from TPS, PCL and PLA were prepared by melt extrusion and injection molding. Blends compositions were varied by 25 %wt of each component. The results indicated immiscible systems with both reduced viscosities and mechanical properties compared to those of neat PCL and PLA. Strategies of compatibilization between TPS and PCL and PLA were evaluated by the production and test of PCLgMA and PLAgMA in the blends with 50 and 75 %wt TPS. The using of PCLgMA in TPS/PCL 50/50 and 75/25 was effective in modifying their tensile properties. The compatibilized blends presented elongation at break up to 230%, and also better dispersion and smaller domains of TPS phase. NWCg and NWCm were obtained by acid hydrolysis using H2SO4 at 45 °C, varying the hydrolysis time from 15 up to 75 min. MET analysis showed the rod-like aspect and nanometric dimensions of NWC. The higher values of aspect ratio (L/D) were find on those NWC obtained from 45 min acid hydrolysis, and their thermal stability was suitable to be incorporated in a TPS/PCL matrix. The nanocomposites were obtained from the compatibilized blend of TPS/PCL 75/25 and NWCg by melt extrusion and injection molding using different contents of NWCg. The NWCg did not interfered on thermal stability of the material. On the other hand, NWCg increased their viscosities and water absorption resistence, as well some of mechanical properties. Both tensile strength and young’s modulus were dramatically increased, respectively 80% and 5 times, with only 1,8 %wt of NWCg added.